2009
DOI: 10.1007/s11235-009-9220-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of unslotted CSMA/CA in wireless networks

Abstract: In this paper a novel analytical model for the saturation throughput of unslotted Carrier Sensing Multiple Access with Collision Avoidance (CSMA/CA) in wireless networks is proposed. A fixed point procedure is developed based on the interaction of the Physical layer (PHY) and the Medium Access Control sub-layer (MAC). The output of the Clear Channel Assessment (CCA), i.e. idle or busy medium in the neighborhood of a node, serves as a feedback mechanism for the dynamical scheduling rate controlled by the back-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 25 publications
1
25
0
1
Order By: Relevance
“…In [18], the authors proposed a novel analytical model of the unslotted CSMA saturation throughput using a semi-Markov process that retrieves the interaction between MAC and PHY layers to derive the CCA output. Performance evaluation showed that the probability that CCA succeeds (respectively fails) clearly depends on the actual backoff stage.…”
Section: Analysis Of the Beaconless Ieee 802154 Schemementioning
confidence: 99%
“…In [18], the authors proposed a novel analytical model of the unslotted CSMA saturation throughput using a semi-Markov process that retrieves the interaction between MAC and PHY layers to derive the CCA output. Performance evaluation showed that the probability that CCA succeeds (respectively fails) clearly depends on the actual backoff stage.…”
Section: Analysis Of the Beaconless Ieee 802154 Schemementioning
confidence: 99%
“…The slotted CSMA/CA backoff algorithm is based on mainly two variables that correspond to: BE , which is the current backoff exponent, and NB , which is used to count the number of backoffs. The detailed algorithm can be seen in many works [31][32][33][34][35][36][37]. In our previous work, we performed an analysis of schedulability with strict real-time constraints and the synchronous mode of the 802.15.4 protocol [13,20].…”
Section: Worst-case End-to-end Delay Flow Control Signals Analysismentioning
confidence: 99%
“…This also leads us to simplifying the calculation of Equation (8), allowing one to know the delay impact (Tm k,i ) of the unslotted CSMA/CA algorithm, taking into account their maximum values of parameters that produce the worst-case transmission message between task k,i and, therefore, Tm k,i = Tm wc , where Tm wc is the worst-case transit delay for all messages sent from task k to task i. Various researches have described how to calculate the effective and actual data rates of an IEEE 802.15.4 wireless network, permitting the calculation of the transmission time between neighbors, giving a very rough estimate for Tm wc [33][34][35], which is approximated to Tm wc = 385.308 ms between two neighboring nodes that employ the WiSe mote [38] for wireless microcontrollers, allowing us to reduce the calculation for each flow of the control loop to:…”
Section: Worst-case End-to-end Delay Flow Control Signals Analysismentioning
confidence: 99%
“…Therefore, if the packet generation time were lower than that taken for the CSMA-CA plus the propagation time, then the client would fill its buffer faster than it can empty it. According to [48] this time is estimated to 6.09 ms. This is comparable to the packet generation time relative to a client rate of 150 requests per second.…”
Section: Workloadmentioning
confidence: 99%